Recovery of biomolecules from marinated herring (Clupea harengus) brine using ultrafiltration through ceramic membranes. Issue 1 (September 2015) - Gringer, Nina; Hosseini, Seyed Vali; Svendsen, Tore; Undeland, Ingrid; Christensen, Morten Lykkegaard; Baron, Caroline P.
Abstract Marinated herring processing brines, which are usually discarded, are rich in salt, protein, non-protein nitrogen, iron, fatty acids, antioxidant and even possess enzymatic activity. This study investigated the performance of ceramic ultrafiltration of two herring spice brines with a major focus on recovery of high value biomolecules such as proteins, fatty acids, minerals, and phenolic compounds. Chemical and biological oxygen demand (COD, BOD5) as well as total suspended solids (TSS) were also measured to follow the performance of the ultrafiltration. The retentates contained 75–82% (<62.7 mg/mL) of the protein and 75–100% of the fatty acids compared to the level in the initial brines. The nitrogen concentration was approximately halved in the permeate, whereas the phosphorous content was significantly increased in the permeate compared to the initial brines. Moreover, a retention of up to 42% COD, >95% TSS and >85% iron was obtained using the ceramic membranes. The two permeates generated were both fat-free and contained approx. 2% of the proteins compared to the unfiltered brines, and the retention of the phenolic compounds were ranged from 0 to 39%. The results presented in this work demonstrate that ceramic ultrafiltration can recover biomolecules from marinated herring brines although pre-filtration optimization is still needed.